Administration, société et pouvoir à Thèbes sous la XXIIe dynastie bubastite - Payraudeau, Frédéric (Bibliotheque d'Etude, 2014)
"This work ... proposes a socio-political history of Egypt during the Libyan Period (XXIInd Dynasty, c. 943-730 BC) through an intensive case study of the city of Thebes. The study presents a chronological analysis of this often disturbed period and includes prosopographical research on local families and an administrative history using titles of state officials. The study of the complex relationships maintained by the royal powers within Theban society, and the analysis of the structures of this society in the light of the anthropology, highlight the originality of this period and the continuity of the royal and state traditions in the Egyptian History of the First Millennium BC."--Back cover.